2022
DOI: 10.1177/00469580211047045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pro-Environmental Prenatal Education Program on Pregnant Women’s Environmental Health Awareness and Behaviors based on the Protection Motivation Theory

Abstract: This study aimed to verify whether a pro-environmental prenatal education program has an effect on pregnant women’s environmental health awareness and behaviors in Korea. This quasi-experimental study employed a nonequivalent control group and nonsynchronized design based on the protection motivation theory as a theoretical framework. In total, 96 pregnant women had their data collected and analyzed in Korea (40 in the experimental group; and 56 in the control group). Data collection through self-reported ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Also naturalist and social scientists’collaboration might play an important role in developing awareness about environmental risk factors [ 50 ]. Confirming our hypothesis, a previous quasi-experimental study in Korea showed that pregnant women having the pro-environmental prenatal education program including motivational education on eco-environmental protection had positive changes in environmental health perceptions and behaviors [ 51 ]. Similarly, the PREVED (PREgnancy, preVention, Endocrine Disruptors) project in France was developed to improve knowledge, to enhance risk perception, and to change exposure behavior by sharing know-how/experience in a positive non-alarmist approach [ 52 ].…”
Section: Discussionsupporting
confidence: 81%
“…Also naturalist and social scientists’collaboration might play an important role in developing awareness about environmental risk factors [ 50 ]. Confirming our hypothesis, a previous quasi-experimental study in Korea showed that pregnant women having the pro-environmental prenatal education program including motivational education on eco-environmental protection had positive changes in environmental health perceptions and behaviors [ 51 ]. Similarly, the PREVED (PREgnancy, preVention, Endocrine Disruptors) project in France was developed to improve knowledge, to enhance risk perception, and to change exposure behavior by sharing know-how/experience in a positive non-alarmist approach [ 52 ].…”
Section: Discussionsupporting
confidence: 81%
“…When presenting a study’s methodology, researchers may choose to apply a study specific format for example, 56 - 58 while others may apply a more formal (eg, PRISMA, JARS) format (eg, Beigel et al, 59 Zeidabadi et al, 60 Kim and Jeong, 61 and DeDonno et al 62 Based on the present studies design, the methodology is reported based on the Journal Article Reporting Standards (JARS), offered by the American Psychological Association. 63 …”
Section: Methodsmentioning
confidence: 99%
“…The effect size (Cohen's d) for the difference between the intervention and control group in primary outcomes was calculated based on a previous study [30]. [17], this study adopted a more conservative rate of 10%. In conclusion, 40 subjects will be recruited for each group.…”
Section: Sample Sizementioning
confidence: 99%
“…Among various approaches to internet-based interventions, mobile applications are particularly feasible and accessible [16]. However, few studies have explored the possibility of promoting environmental health behaviors among pregnant women via a mobile application intervention, although one study was conducted on an intervention using online lectures and cartoon comics [17]. Hence, this study aimed to test the effectiveness of a mobile application intervention named "DECO-MOM" (DEep Ecology-MOM) for pregnant women.…”
Section: Introductionmentioning
confidence: 99%